2011
DOI: 10.1371/journal.pone.0026506
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Changes in Plant Community Composition under 3-Decade Grazing Exclusion in Continental Steppe

Abstract: An understanding of the factors controlling plant community composition will allow improved prediction of the responses of plant communities to natural and anthropogenic environmental change. Using monitoring data from 1980 to 2009, we quantified the changes in community composition in Leymus chinensis and Stipa grandis dominated grasslands in Inner Mongolia under long-term grazing-exclusion and free-grazing conditions, respectively. We demonstrated that the practice of long-term grazing exclusion has signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 25 publications
(33 reference statements)
3
34
0
Order By: Relevance
“…Zhao et al (2008) have demonstrated that the combination of N addition and grazing promotes revegetation, and triggers the compensatory growth of plants by accelerating the N cycle and eliminating N accumulation. N addition significantly affects the restoration process of degraded grassland patches and might be augmented by moderate grazing, and the combination of these methods should be considered as a new approach for grassland restoration (He et al, 2011).…”
Section: [ ( F I G _ 5 ) T D $ F I G ]mentioning
confidence: 99%
“…Zhao et al (2008) have demonstrated that the combination of N addition and grazing promotes revegetation, and triggers the compensatory growth of plants by accelerating the N cycle and eliminating N accumulation. N addition significantly affects the restoration process of degraded grassland patches and might be augmented by moderate grazing, and the combination of these methods should be considered as a new approach for grassland restoration (He et al, 2011).…”
Section: [ ( F I G _ 5 ) T D $ F I G ]mentioning
confidence: 99%
“…combined impact on grassland plant diversity. For example, He et al (2011) showed that plant diversity in different grassland types has diverse responses to litter that accumulates under grazing exclusion. Therefore, to explore the mechanisms that underlie changes in the plant diversity of grasslands, it is necessary to obtain a better understanding of how grazing exclusion affects plant diversity in grasslands with different types of vegetation, climate, nutrients, and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Livestock exclosures have a potential value in assessing the effects of grazing upon vegetation and C sequestration in the grasslands (Bock et al, 1984;Cheng et al, 2011;He et al, 2011;Li et al, 2012;Su et al, 2003). Exclosures appear to favor higher community diversity and productivity compared with grazing in the arid grasslands (Bock et al, 1984;Cheng et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, grazing exclosures are widely used as a management practice to restore degraded grasslands Su et al, 2003). However, recent studies on a fenced Leymus chinensis grassland in northern China demonstrated that the outcomes from exclosure were related to the community types of the grasslands, with responses to litter accumulation dependent on plant density (He et al, 2011). Generally, there were cascade effects on C sequestration in the plant-soil system from variations of the community structure and other factors related to exclosure Su et al, 2003).…”
Section: Introductionmentioning
confidence: 99%